Building a Sustainable Future Through Physiotherapy and Environmental Health (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
The growing impact of climate change, environmental degradation, and unsustainable health systems has intensified the need to rethink healthcare practices through the lens of planetary health. Physiotherapy, as a profession focused on functional recovery, health promotion, and prevention, is uniquely positioned to contribute to more sustainable healthcare systems while simultaneously addressing environmental determinants of health. Integrating environmental health principles into physiotherapy practice can support both individual wellbeing and broader ecological sustainability.This perspective paper explores the intersection between physiotherapy and environmental health, highlighting how rehabilitation professionals can actively contribute to sustainable health systems. Key pathways include promoting low-carbon models of care such as active mobility, community-based rehabilitation, outdoor therapeutic interventions, and resource-efficient clinical practices. Physiotherapists also play a critical role in mitigating the health impacts of environmental challenges, including air pollution, heat stress, climate-related disasters, and the increasing burden of chronic non-communicable diseases exacerbated by environmental factors.Furthermore, the integration of sustainability principles into physiotherapy education, research, and clinical practice is discussed. Emerging approaches such as environmentally informed clinical decision-making, sustainable rehabilitation pathways, and the use of digital technologies to optimise care delivery can reduce the environmental footprint of healthcare while maintaining high standards of patient outcomes. These strategies align with global frameworks such as the Sustainable Development Goals (SDGs), One Health, and Planetary Health.Building a sustainable future through physiotherapy requires interdisciplinary collaboration, policy engagement, and the development of evidence-based models that incorporate environmental considerations into rehabilitation practice. By embracing its role within environmental health, physiotherapy can contribute not only to improved patient outcomes but also to the resilience and sustainability of health systems and communities.Keywords: Planetary health; environmental physiotherapy; sustainable healthcare; climate change and health; rehabilitation and sustainability